Proceedings of the 20th Annual International Conference on Mobile Computing and Networking 2014
DOI: 10.1145/2639108.2639116
|View full text |Cite
|
Sign up to set email alerts
|

Exploring human mobility with multi-source data at extremely large metropolitan scales

Abstract: Expanding our knowledge about human mobility is essential for building efficient wireless protocols and mobile applications. Previous human mobility studies have typically been built upon empirical single-source data (e.g., cellphone or transit data), which inevitably introduces a bias against residents not contributing this type of data, e.g., call detail records cannot be obtained from the residents without cellphone activities, and transit data cannot cover the residents who walk or ride private vehicles. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(66 citation statements)
references
References 14 publications
1
65
0
Order By: Relevance
“…One intuitive idea is to improve the existing models by integrating bike-sharing data. In [15], authors have demonstrated the reduced bias of mobility modeling by exploiting the inherent diversities from multi-source data (i.e., taxi, bus, subway and smartphone CDR).…”
Section: Mobility Model Fusion With Multi-source Datamentioning
confidence: 99%
See 1 more Smart Citation
“…One intuitive idea is to improve the existing models by integrating bike-sharing data. In [15], authors have demonstrated the reduced bias of mobility modeling by exploiting the inherent diversities from multi-source data (i.e., taxi, bus, subway and smartphone CDR).…”
Section: Mobility Model Fusion With Multi-source Datamentioning
confidence: 99%
“…In addition to bike-sharing data, researchers analyzed human mobility based on other empirical data from taxicabs [36], buses [37], subways [38], private cars [39], WiFi APs [40,41], cellular carriers [15,42] and social networks [43]. Due to the unique intrinsic properties such as the decentralized structure, ondemand usage and unattended vehicles in BSS, our work provides a fundamentally different model from these designs.…”
Section: Related Workmentioning
confidence: 99%
“…Zheng and Xie () have argued that more experienced tourists should be given more weight when extracting attractive travel sequences. The diversity‐attentive popularity indicator can therefore be compelling, because the inclusion of the number of tracks in the cost function can be interpreted as giving more weight to the tracks of frequent cyclists.…”
Section: Discussionmentioning
confidence: 99%
“…Tao et al [13] demonstrated a multistage ways in order to render more insightful spatial-temporal patterns of urban public transport (UPT) passenger's behavior. Zhang et al [14] proposed and implemented a novel architecture called mPat to investigate people movement utilizing various data source, including SCD feeds from 24 thousands vehicle, 16 million smart cards and 10 million cellphones. Yen et al [15] explored the effects of the two principal features of the fare policies applied in SEQ, using smart card transaction records.…”
Section: Literature Reviewmentioning
confidence: 99%